PROFILE OF PEER INTERACTION IN CLASS XI AT SMAN 9 SIJUNJUNG: PROFIL INTERAKSI TEMAN SEBAYA PADA KELAS XI DI SMAN 9 SIJUNJUNG - Inatan Dwi Wulandari; Zulkifli; Rici Kardo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research is motivated by the lack of ability to interact between peers. The purpose of this study is to describe the profile of peer interaction as seen from: 1) Imitation factors. 2) Suggestion factors. 3) Identification factors. 4) The sympathy factor. This research is a type of quantitative descriptive research. The population in this study is 103 students. The sample of this study amounted to 103 students. Sampling uses the total sampling technique. The instrument used was in the form of a questionnaire, and analyzed using the percentage technique.